Constitutional Duplication of a Region of Chromosome Yp Encoding AMELY, PRKY, and TBL1Y : Implications for Sex Chromosome Analysis and Bone Marrow Engraftment Analysis - Murphy, Kathleen M. (American Society for Investigative Pathology, 2007)
Amelogenin has chromosome X (AMELX) and Y (AMELY) homologs that can be differentiated based on the length of polymerase chain reaction (PCR) amplification products. In addition to being useful for gender identification, analysis of amelogenin has utility for monitoring bone marrow engraftment in patients after a sex-mismatched bone marrow transplant, characterizing sex chromosome abnormalities, and for forensic purposes for analyzing mixtures of male and female DNA. Here, we describe two brothers in which PCR analysis demonstrated twofold greater AMELY products compared with AMELX products. Karyotype and X/Y fluorescence in situ hybridization analysis demonstrated a single copy of the X and Y chromosomes without any identifiable abnormalities. Oligonucleotide comparative genomic hybridization array analysis demonstrated a duplication of a portion of chromosome Yp that encompassed a region of at least 2.6 Mb but not greater than 4.0 Mb. The amplified region contains the genes AMELY, transducin (β)-like 1 protein Y (TBL1Y), and protein kinase Y (PRKY). To our knowledge, duplication of this region has not previously been reported. The family history is unremarkable, and the brothers are without ap-parent dysmorphic features. Although this and other genetic variants involving AMELY are uncommon, one should use caution when using amelogenin for sex chromosome analysis and bone marrow engraftment analysis.